Pengaruh Harga dan Kualitas Pelayanan terhadap Keputusan Pembelian pada PT. Sari Melati Kencana Pematangsiantar - Arwin Arwin; Debora Silvia Hutagalung (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
The rapid development of the business world has resulted in increasingly fierce competition, so that various ways are used by business actors to maintain and develop a competitive advantage with its competitors. In the era of modernization like today, a practical and instantaneous lifestyle has developed which affects almost the entire human population in the world. Instant lifestyle is a lifestyle that prioritizes practicality, speed and time efficiency. For some people, fast, practical and efficient have become the main needs in their daily activities. This certainly has an effect on business competition, which is then responded by most manufacturers in designing products that suit the needs of people's instant lifestyles. A business that is influenced by people's lifestyle is the restaurant business of PT. Sari Melati Kencana Pematangsiantar. Data collection methods used in this research are questionnaires, interviews, documentation and observation. The population in this study was 40 people and the number of samples in this study was 40 people because the sampling technique in this study was the census method. The data analysis technique used was the instrument test, namely validity and reliability tests, classic assumption tests, namely normality tests and hypothesis tests, namely multiple linear regression, correlation coefficient, determination coefficient, partial test (t test), and simultaneous test (F test). The results showed that: (1) price has a positive effect on purchasing decisions, this is evidenced by the value of tcount> ttable (4.452> 2.026) with a significance value of 0.000 (sig ≤ 0.05), (2) service quality has a positive effect on the decision. purchases with tcount> ttable (7,401> 2,026) with a significance value of 0,000 (sig ≤ 0.05), (3) price and service quality have a positive effect on purchasing decisions, this is evidenced by the value of Fcount> Ftable (49.320> 3, 25) with a significance value of 0.000 (sig ≤ 0.05)